Literasi Keuangan Digital dan Pemasaran Digital Bagi Peningkatan Usaha Kelompok Pengolah dan Pemasar (Poklahsar) Global Milkfish Semarang - Widyarti, Maria Th. Heni; Hasanudin, Mohamad; Karyanti, Tutik Dwi; Widiart, Ardian; Pinanditho, Kenneth; Arbainah, Siti; Korawijayanti, Lardin (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
The Global Milkfish Processing and Marketing Group (Poklahsar) located in Kampung Sentra Bandeng has been proven to improve the welfare of the surrounding community and is able to absorb workers in the area. However, in its operations it has not implemented digital financial management and marketing. With an understanding of digital marketing, it is hoped that the sales prospects for processed milkfish products can reach a wider market. This study uses a qualitative approach with a participatory method to understand the needs and challenges faced by the Semarang Global Milkfish Processing and Marketing Group (POKLAHSAR) in adopting digital financial literacy and digital marketing. Descriptive statistical analysis techniques are also used to support the interpretation of relevant quantitative data, such as the level of member involvement in training and changes in the use of digital media. Based on the results of the activity, out of 20 MSMEs, 7 MSMEs (35%) have implemented conventional financial management and the rest have not. After the activity, all 20 MSMEs (100%) were able to implement digital business financial management because they had been equipped and given an MSME financial management template using Microsoft Excel. Participants now have better abilities in utilizing social media to promote their products more effectively. Before the activity, only 5 MSMEs (25%) out of 20 MSMEs utilized digital marketing. After the activity, 20 MSMEs already had their own social media, and 5 MSMEs (25%) started implementing advertising through social media.ABSTRAKKelompok Pengolah dan Pemasar (Poklahsar) Global Milkfish yang berlokasi di Kampung Sentra Bandeng terbukti meningkatkan kesejahteraan Masyarakat sekitar dan mampu menyerap tenaga kerja disekitar daerah tersebut. Namun, dalam operasinya belum menerapkan pengelolaan keuangan dan pemasaran digital. Dengan pemahaman pemasaran digital diharapkan prospek penjualan produk olahan bandeng bisa menjangkau pemasaran yang lebih luas. Penelitian ini menggunakan pendekatan kualitatif dengan metode partisipatif untuk memahami kebutuhan dan tantangan yang dihadapi oleh kelompok Pengolah dan Pemasar (POKLAHSAR) Global Milkfish Semarang dalam mengadopsi literasi keuangan digital dan pemasaran digital. Teknik analisis statistik deskriptif juga digunakan untuk mendukung interpretasi data kuantitatif yang relevan, seperti tingkat keterlibatan anggota dalam pelatihan serta perubahan penggunaan media digital. Berdasarkan hasil kegiatan, dari 20 UMKM, 7 UMKM (35%) sudah menerapkan pengelolaan keuangan konvensional dan sisanya belum. Setelah kegiatan, seluruh 20 UMKM (100%) sudah dapat menerapkan pengelolaan keuangan usaha digital karena sudah dibekali dan diberikan template pengelolaan keuangan UMKM menggunakan Microsoft Excel. Peserta kini memiliki kemampuan yang lebih baik dalam memanfaatkan media sosial untuk mempromosikan produk mereka secara lebih efektif. Sebelum kegiatan hanya 5 UMKM (25%) dari 20 UMKM yang memanfaatkan pemasaran digital. Setelah kegiatan 20 UMKM sudah memiliki sosial media masing-masing, serta 5 UMKM (25%) mulai menerapkan iklan melalui sosial media.